PENGARUH SENI TARI BERBASIS TEMA TERHADAP MOTORIK KASAR ANAK KELOMPOK B DI TK NEGERI PEMBINA LAHAT - Ani Safitri; Hasmalena hasmalena; Rukiyah Rukiyah (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2017)
This research entitled The Influence of Dance-Based Arts Theme Against Motoric Coarse Children Group B In Tk Country Pembina Lahat with Research Type Semu design One Shoot Case Study. The sampling technique used is purposive sampling with the consideration of the crude motor skills that are still low in class B which amounts to 31 children, 18 boys and 13 girls. Based on the results of t test obtained t data 4.03 while ttabel 1.70 with ? = 0.05 and dk = 30 means it can be concluded that there is influence of Dance Berbasi Theme of Motorik rough child group B in TK Negeri Pembina Lahat. So Ha accepted and Ho rejected. Rough Motoric Indicators of Children with Dance-Based Arts Themes observed are the agility of children dancing with the help of songs planting corn and the sun, children dancing with agility as per the motion provided, the balance of the child's body position and the coordination of the child's movement while dancing. Motorik Kasar children of 14 children included in the category developed very well (BSB) with the percentage of 45.16%, 11 children included in the category developed as expected (BSH) with a percentage of 35.48%, then as many as 4 children included in the category began to develop (MB) with a percentage of 12.90% and as many as 2 children included in category not yet developed (BB) with 6.4% percentage.